Magnetic field enhancement of organic photovoltaic cells performance - S. Oviedo-Casado (Nature Portfolio, 2017)
Abstract Charge separation is a critical process for achieving high efficiencies in organic photovoltaic cells. The initial tightly bound excitonic electron-hole pair has to dissociate fast enough in order to avoid photocurrent generation and thus power conversion efficiency loss via geminate recombination. Such process takes place assisted by transitional states that lie between the initial exciton and the free charge state. Due to spin conservation rules these intermediate charge transfer states typically have singlet character. Here we propose a donor-acceptor model for a generic organic photovoltaic cell in which the process of charge separation is modulated by a magnetic field which tunes the energy levels. The impact of a magnetic field is to intensify the generation of charge transfer states with triplet character via inter-system crossing. As the ground state of the system has singlet character, triplet states are recombination-protected, thus leading to a higher probability of successful charge separation. Using the open quantum systems formalism we demonstrate that the population of triplet charge transfer states grows in the presence of a magnetic field, and discuss the impact on carrier population and hence photocurrent, highlighting its potential as a tool for research on charge transfer kinetics in this complex systems.